1999
DOI: 10.1128/jb.181.6.1739-1747.1999
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Aminotransferase Catalyzes the Final Step of Methionine Recycling in Klebsiella pneumoniae

Abstract: An aminotransferase which catalyzes the final step in methionine recycling from methylthioadenosine, the conversion of α-ketomethiobutyrate to methionine, has been purified fromKlebsiella pneumoniae and characterized. The enzyme was found to be a homodimer of 45-kDa subunits, and it catalyzed methionine formation primarily using aromatic amino acids and glutamate as the amino donors. Histidine, leucine, asparagine, and arginine were also functional amino donors but to a lesser extent. The N-terminal amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Finally, the role of amino acid transaminases in MOB transamination in yeast seems to be an intriguing question, as different isoenzymes may have different roles in different conditions, resulting in a very robust step of the cycle. We have clearly demonstrated that the aromatic and branched chain amino acid transaminases are the main enzymes for this step, similar to the situation in bacteria [12][13][14][15]. Thus, all of the enzymes in the methionine salvage pathway have been identified in a eukaryotic organism.…”
Section: Discussionsupporting
confidence: 66%
“…Finally, the role of amino acid transaminases in MOB transamination in yeast seems to be an intriguing question, as different isoenzymes may have different roles in different conditions, resulting in a very robust step of the cycle. We have clearly demonstrated that the aromatic and branched chain amino acid transaminases are the main enzymes for this step, similar to the situation in bacteria [12][13][14][15]. Thus, all of the enzymes in the methionine salvage pathway have been identified in a eukaryotic organism.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, we presume that these three steps, dehydration, enolization and dephosphorylation, may be performed by a single enzyme in higher plants. In addition, we suppose that IDI4, the putative aspartate/tyrosine/aromatic aminotransferase induced by Fe deficiency, is a candidate enzyme for the final step of the methionine cycle (Berger et al, 2003;Heilbronn et al, 1999). It has been confirmed by Northern blot analysis that transcript levels of all the candidate genes participating in this pathway (Figure 7) were increased in Fe-deficient rice roots .…”
Section: Genes Involved In the Methionine Cycle Are Upregulated By Znmentioning
confidence: 71%
“…The expression of these genes also increased dramatically in response to Fe deficiency, with induction ratios higher than those in response to Zn deficiency. Putative aspartate/tyrosine/aromatic aminotransferase (IDI4, accession number AB206815), which has been predicted to be the enzyme that catalyze the conversion of 2-keto-4-methylthiobutyric acid (KMTB) to methionine by transamination (Berger et al, 2003;Heilbronn et al, 1999), was also upregulated by Zn deficiency and Fe deficiency. Methylthioribose (MTR) kinase was upregulated by Fe deficiency but not by Zn deficiency.…”
Section: Microarray Analysis Of Gene Expression In Barley Roots In Rementioning
confidence: 99%
“…suggesting that it is a plant TAT with multi-substrate specificity. Some microbial TATs also have a broad substrate specificity, including TATs from Klebsiella pneumoniae (Heilbronn et al, 1999), Bacillus sp. (Berger et al, 2003), and Trypanosoma cruzi (Nowickia et al, 2001), which deaminate Tyr (3) as well as other aromatic and aliphatic amino acids.…”
Section: Attat1 and Attat2 Have Distinct Substrate Specificity And Prmentioning
confidence: 99%